(untitled) (Bangladesh Rice Journal, 2020)
Cold stress affects growth and development of rice plants from germination to reproductive stages. Thirty breeding lines/varieties including tolerant and susceptible check varieties were evaluated for cold tolerance at seedling and reproductive stage using artificially induced low temperature situations to understand the genetic relationship among them and to identify promising donors for cold tolerance. Three breeding lines, BR8253-9-3-4-3, IR77497-31-2-3-1and IR2266-42-6-2 demonstrated higher cold tolerance for the seedling stage (LD score <3.0). Molecular analysis revealed 68% genetic similarity among the genotypes. On average 64% of the breeding lines shared common alleles at any given locus ranging from 27% (RM22870) to 97% (RM186). UPGMA dendrogram showed that majority of the breeding lines showing 4-5 degrees of LD were grouped together. Two breeding lines, BR8258-7-1-5-2B2 and BR8258-7-1-5-2B3 having 86% common alleles showed low leaf discoloration (LD: 4) at seedling stage coupled with relatively low reduction in spikelet fertility (45.8% and 48.1%) and grain yield (43.3% and 39.1%). The gene diversity and PIC value revealed that seven SSR loci (RM1282, RM600, RM5349, RM6972, RM5847, RM5911, and RM511) might be the best markers to differentiate between tolerant and susceptible genotypes at reproductive stage. The breeding lines with tolerance to cold stress at the seedling and the reproductive stages identified from this study, and the SSR markers mentioned above could be useful for developing cold tolerance rice. Bangladesh Rice j. 2019, 23(2): 1-15